El uso del tetralema como una herramienta para abordar una segunda reflexividad inclusiva. La experiencia aportada por la investigación participativa sobre las miniqueserías artesanales de Tenerife - González Rodríguez, Pilar (Cuadernos de Trabajo Social, 2006)
In this paper, we present the underlying ideas of our attempt to work on local development with participatory methodologies to build a happier society. In the first part we consider theoretical matters in order to, in the second part, put forth an experience on the use of the tetralemma in participatory research on Micro Craft Cheese Makers of Tenerife.
Keywords: System; Sustainable development; Citizen participation; Democracy; Culture; Tetralemmma; Participatory research